Pengaruh Psychological Capital dan Occupational Future Time Perspective terhadap Turnover Intention Karyawan - Agung K. Rahayu; Silverius Yoseph Soeharso; Aisyah (Jurnal Ilmiah Psikologi MIND SET, 2016)
A survey as cited by one of the multinational companies in Indonesia showed that 60% of the generation of Indonesian young adults had been resigned from their jobs within three years of work. Turnover behavior begins with intention which becomes turnover intention, an important thing to be a strong predictor of turnover. Previous research showed there was a significant negative relationship between psychological capital and turnover intention. Turnover intention could be affected by the occupational future time perspective, which can affect personal choices and actions. The purpose of this study was to determine whether there is significant influence between psychological capital and occupational future capital time perspective to turnover intention on young adult employees. This study used a quantitative approach. Samples of this research were 146 respondents which are 48% males and 52% females. Analysis showed that the significant effect of psychological capital and occupational future time perspective altogether to turnover intention. Practical suggestion for the companies to develop their employees' psychological capital, so they can facilitate employees' motivation and behavior intention to reach a better performance which will make a good impact for their companies as well.